2021
DOI: 10.2174/0929866527666200910164118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Seed Proteome Profile of Wild and Cultivated Chickpeas of India

Abstract: Background: Chickpea is a widely grown legume in India, Australia, Canada, and Mediterranean regions. Seeds of chickpea are good source of protein for both human and animals. Wild relatives of chickpea (Cicer arietinum) are the potential gene pool for crop improvement; however, very little information is available on the seed proteome of these wild chickpeas. Objective: We aimed to analyze the seed proteome profiles of three wild relatives of chickpea, Cicer bijugum, Cicer judaicum and Cicer microphyllum al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Mass spectrometry-based proteomics combined with advanced bioinformatics is a powerful platform not only to determine the seed proteome profile from many legumes but also to identify, quantify, and demonstrate the conformational changes of many allergenic proteins. Despite being a crop high in nutrients, research has shown that mung beans are also cross-reactive with IgE. ,, Previous findings verified both naso-bronchial sensitization and the allergic reaction to mung bean consumption in clinical samples. ,, To date, only a handful of research papers have been published on the mung bean proteome. , However, to the best of our knowledge, no comparative analysis of the mung bean cultivar-specific seed proteome has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry-based proteomics combined with advanced bioinformatics is a powerful platform not only to determine the seed proteome profile from many legumes but also to identify, quantify, and demonstrate the conformational changes of many allergenic proteins. Despite being a crop high in nutrients, research has shown that mung beans are also cross-reactive with IgE. ,, Previous findings verified both naso-bronchial sensitization and the allergic reaction to mung bean consumption in clinical samples. ,, To date, only a handful of research papers have been published on the mung bean proteome. , However, to the best of our knowledge, no comparative analysis of the mung bean cultivar-specific seed proteome has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high nutritional value of the chickpea, there is little information on it at its protein-level [ 24 , 25 ]. Information has been mainly obtained using a combination of chromatography, SDS-PAGE, and mass spectrometry, and suggests that the subunit molecular characteristics of globulins and albumins in chickpeas are comparable to those of other legumes.…”
Section: Introductionmentioning
confidence: 99%